The Conversion Kinetics of Tincal to Boric Acid in Nitric Acid Solutions - Mehmet, Tunc; Hasan, Irem; Muhtar, M. Kocakerim; Çopur, Mehmet; Ozkan, Kucuk (Jihad Daneshgahi, 2020)
Pure borax and various boron compounds are produced from the solutions in which tincal is dissolved with various reagents. Economically important boron compounds such as boric acid, borax, boric oxide, and refined hydrated sodium borates and perborates are produced from boroncontaining ores. The production of boric acid by using nitric acid from tincal is more advantageous because it evaluates by-product NaNO3 as fertilizer production. In this study, the conversion kinetics of tincal to boric acid in nitric acid solutions were investigated by such parameters as particle size, 300-1500 mu m; acid concentration,0.5-4 mol/L; solid-to-liquid ratio 0.04-0.10 g/mL; stirring speed 20.93-62.8 s(-1), and reaction temperature, 30-60 degrees C. The conversion was found to increase with decreasing particle size and solid-to-liquid ratio and while it increased with increasing reaction temperature, acid concentration, and stirring speed. The conversion kinetics was examined using the heterogeneous and pseudo-homogeneous reaction models. The experimental results were found to be in better agreement with the correlation given in the following equation and the activation energy being 37.5 kJ/mol. ln(1-XHNO3/1-X-tincal)=(C-0,C-HNO3, 2C(0,tincal))kt
Keywords: Borax; Conversion kinetics; Nitric acid; boric acid